(untitled) (Collection of scientific works «Modern structures of metal and wood», 2022)
One of the modern directions in construction is the development of multistorey buildings, in which the main part of the structural elements is made of timber, and spatial stability is provided by reinforced concrete diaphragms or a stiffening core. A possible problem when using different materials in load-bearing structures is a significant difference in deformation characteristics and the effect of creep. The article presents the results of theoretical studies of the effect of concrete and wood creep on the stress-strain state of timber-reinforced concrete multistorey buildings. A square in plan prototype building with a frame system, load-bearing timber structures (glued laminated timber and LVL) and a reinforced concrete stiffening core was taken for the analysis. The number of floors was varied from 5 to 20 (the height of the options under consideration was 15-60 m). To take into account the creep of concrete, the Eurocode EN 1992-1-1 model was used, and the T. Toratti model of an elastic-viscous-plastic body was adopted for timber. When determining the creep characteristics, the conditions corresponding to service class 1 (55% relative humidity) and 2 (65% relative humidity) were considered. It has been established that during 50 years, the values of vertical displacements obtained taking into account creep increase several times compared to the results for the elastic model: under conditions of service class 1 by 2.6–3.7 times for laminated timber columns; by 1.8-3.1 times for LVL columns and by 3.3-3.4 times for reinforced concrete stiffening core; under the conditions of service class 2 by 2.4-3.7 times for laminated timber columns; by 1.8-2.9 times for LVL columns and by 3.05-3.15 times for reinforced concrete core. An analysis of the nature of the deformation of the considered variants showed that the magnitude of vertical displacements differs significantly for timber columns and a reinforced concrete stiffening core. Non-uniform deformation of vertical structures causes a redistribution of forces between the frame elements, leads to a skew of the storey and the appearance of additional longitudinal tensile forces in the floor beams.